A Very Short Be–Be Distance but No Bond: Synthesis and Bonding Analysis of Ng–Be2O2–Ng′ (Ng, Ng′=Ne, Ar, Kr, Xe). Issue 9 (23rd January 2017) - Zhang, Qingnan; Li, Wan‐Lu; Zhao, Lili; Chen, Mohua; Zhou, Mingfei; Li, Jun; Frenking, Gernot
Abstract: Short interatomic distances below standard values for a single bond are usually identified with double or triple bonds. The synthesis and spectroscopic characterization of a molecule is reported where the distance between two beryllium atoms is shorter than a standard double bond but there is no bond. The cyclic diberyllium dioxide Be2 O2 molecule, which is coordinated by two noble gas atoms in Ng−Be2 O2 −Ng′ (Ng, Ng′=Ne, Ar, Kr, Xe) was isolated and spectroscopically identified in low‐temperature matrices. The complexes possess very short Be−Be distances, but the analysis of the electronic structure reveals that there is no chemical bond. Abstract : Faraway, so close ! The homo‐ and heteroleptic noble gas complexes Ng−Be2 O2 −Ng′ (Ng, Ng′=Ne, Ar, Kr, Xe) that were prepared in low‐temperature matrices possess a cyclic Be2 O2 core with Be−Be distances that are shorter than a standard Be=Be double bond without a chemical bond.